The integration of psychoeducation, anti-corruption education and christian family education for the fathers of GMIT Laharoi - Friandry Windisany Thoomaszen; Sance Mariana Tameon (Integritas: Jurnal Antikorupsi, 2022)
Gender, religion and race are becoming important considerations in corruption cases. Various management initiatives must be explored to counter corruption, particularly prevention strategies that originate within the family as the cornerstone of religious, moral and anti-corruption values education. This study discusses anti-corruption education at Evangelical Christian Church in Timor GMIT in the context of religion, Christian families and church. The research focuses on integrating anti-corruption education and Christian family education by including fathers in anti-corruption education. The purpose of the study is to integrate Christian family education and psychoeducation programs as part of an effort to prevent corruption cases involving GMIT Laharoi's fathers. The quasi-experimental design with The Posttest Only Design and Nonequivalent Groups was used as the primary method, and the narrative qualitative approach was used as the complementary method. The Mann-Whitney non-parametric test was employed for quantitative analysis. Participants in the quasi-experiments were 16, with eight subjects in the experimental group and eight in the control group. The Mann-Whitney test findings indicate an Asymp Sig. (2-tailed) of 0.005 0.05, indicating a difference between the experimental and control groups' post-test outcomes. As a result, the study found that integration of anti-corruption education and Christian family education can affect GMIT Lahairoi fathers' understanding and involvement in educating their children.